Expression and Stabilization of Microinjected Plasmids Containing the Herpes Simplex Virus Thymidine Kinase Gene and Polyoma Virus DNA in Mouse Cells - Yamaizumi, Masaru (1983)
To observe the effects of polyoma virus DNA on the expression of the herpes simplex virus (HSV) thymidine kinase (TK) gene early after transfer into TK-deficient mouse cells and the subsequent development of stable TK-positive transformants, we constructed a series of recombinant plasmids containing the herpes simplex virus TK gene joined with various segments of the polyoma virus genome and microinjected them into the nuclei or cytoplasm of LTK-A cells (TK(−), APRT(−)). The frequency of nucleus-injected cells expressing TK after 1 day, measured by autoradiography of cells incubated with [(3)H]thymidine, increased approximately 30-fold when the plasmids contained the polyoma virus origin of replication. The origin includes sequences with homology to the simian virus 40 origin of replication and adjoining sequences, including a recently defined transcription-enhancing sequence. After microinjection of a single origin-containing plasmid molecule per cell, TK expression was detected in approximately 50% of the injected cells. When a larger number of origin-containing plasmid molecules were injected per cell, all cells showed early TK activity. When the entire polyoma virus early region was present, neighboring uninjected cells became TK positive. When plasmids were injected into the cell cytoplasm, approximately 400 times as many molecules per cell were needed to cause early TK activity. The frequency of stable transformation observed 2 weeks after nuclear injection of 10 to 20 polyoma virus origin-containing plasmid molecules per cell was at least 2 orders of magnitude greater than with plasmids containing the TK gene alone. The greatest enhancement of stable TK transformation was obtained with plasmids containing the origin alone, when the maximum frequency of stable transformation was 5%. The addition of the coding regions for the small and medium T antigens or the entire early region significantly decreased TK transformation frequency in a copy-dependent fashion. The timing of stabilization of TK-positive transformation was analyzed by releasing hypoxanthine-aminopterin-thymidine selection pressure at various times after microinjection, culturing the cells in nonselective medium, and assaying for TK activity. Stabilization was found to occur between 3 and 6 days after nuclear injection. Cells injected with a plasmid containing the origin and the early region were examined for expression of the large T antigen with polyoma virus antitumor serum and immunofluorescent staining. The expression of the large T antigen was clearly associated with a cytopathic effect. TK-positive clones observed 2 weeks after injection of the plasmid were uniformly T antigen negative. Cytotoxicity may be the result of plasmid replication and toxic levels of T antigen or TK. In addition, expression of the large T antigen may block stabilization by preventing the integration of origin-containing plasmid molecules.